Recent changes to generic delimitations in the Schismatoglottideae - Sin Yeng, Wong; Peter C., Boyce (International Aroid Society, 2018)
A summary of recent far-reaching changes to generic delimitations in Tribe Schismatoglottideae is provided. Thirty genera are now recognised, comprising 13 pre-existing genera (Apoballis, Aridarum, Bakoa, Bucephalandra, Fenestratarum, Galantharum, Ooia, Phymatarum, Pichinia, Piptospatha, Schismatoglottis, Schottariella and Schottarum), five resurrected genera (Colobogynium, Gamogyne, Heteroaridarum, Hottarum and Rhynchopyle) and 11 newly recognised genera: Bakoaella, Bidayuha, Burttianthus, Gosong, Hera, Kiewia, Nabalu, Pursegloveia, Naiadia, Tawaia and Toga.